2021
DOI: 10.3390/mi12121513
|View full text |Cite
|
Sign up to set email alerts
|

Osmotically Enabled Wearable Patch for Sweat Harvesting and Lactate Quantification

Abstract: Lactate is an essential biomarker for determining the health of the muscles and oxidative stress levels in the human body. However, most of the currently available sweat lactate monitoring devices require external power, cannot measure lactate under low sweat rates (such as in humans at rest), and do not provide adequate information about the relationship between sweat and blood lactate levels. Here, we discuss the on-skin operation of our recently developed wearable sweat sampling patch. The patch combines os… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 66 publications
0
36
0
Order By: Relevance
“…Lost body water must be replaced to maintain normal physiologic processes; this is particularly important for body builders, athletes [ 5 ], firefighters, etc. Furthermore, sweat, like saliva and tears [ 6 ], is noninvasively induced from deeper in the body and carries a diverse array of biomolecules, ranging from small electrolytes (including Na + , K + , and Ca 2+ ) and metabolites (such as glucose, lactate [ 7 ], and ethanol [ 8 ]) to hormones and larger proteins [ 9 ], which may provide vital information about physiological status and fitness level [ 10 ]. Sweat analysis could become an alternative to invasive blood tests in the future [ 11 , 12 ], as Heikenfeld et al [ 13 ] demonstrated—for the first time in vivo—the complete correlation between continuous sweat data and blood data.…”
Section: Introductionmentioning
confidence: 99%
“…Lost body water must be replaced to maintain normal physiologic processes; this is particularly important for body builders, athletes [ 5 ], firefighters, etc. Furthermore, sweat, like saliva and tears [ 6 ], is noninvasively induced from deeper in the body and carries a diverse array of biomolecules, ranging from small electrolytes (including Na + , K + , and Ca 2+ ) and metabolites (such as glucose, lactate [ 7 ], and ethanol [ 8 ]) to hormones and larger proteins [ 9 ], which may provide vital information about physiological status and fitness level [ 10 ]. Sweat analysis could become an alternative to invasive blood tests in the future [ 11 , 12 ], as Heikenfeld et al [ 13 ] demonstrated—for the first time in vivo—the complete correlation between continuous sweat data and blood data.…”
Section: Introductionmentioning
confidence: 99%
“…8−16 Lactate is also present in the blood where its concentration ranges from 0.5 to 2 mM for healthy subjects at rest. 2,8,9 Greater amounts of lactate begin to appear in the blood only when the body experiences high-intensity exertion (>120 W) and crosses the lactate threshold (LT) workout intensity. 2,8 For this reason, the blood lactate concentration can peak up to ∼11 mM upon surpassing the LT. 9 Therefore, under other physiological conditions (e.g., rest or medium exercise workout), the sweat lactate concentration usually ranges ∼2−10 times greater than the blood lactate concentration (∼1−3 mM) and follows a different trend.…”
mentioning
confidence: 99%
“…2,8,9 Greater amounts of lactate begin to appear in the blood only when the body experiences high-intensity exertion (>120 W) and crosses the lactate threshold (LT) workout intensity. 2,8 For this reason, the blood lactate concentration can peak up to ∼11 mM upon surpassing the LT. 9 Therefore, under other physiological conditions (e.g., rest or medium exercise workout), the sweat lactate concentration usually ranges ∼2−10 times greater than the blood lactate concentration (∼1−3 mM) and follows a different trend. 2,8,10 Hence, a minute rise (with respect to rest) in the blood lactate concentration during medium exercise workout suggests that most of the lactate produced via glycolysis in the muscles is released in sweat.…”
mentioning
confidence: 99%
See 2 more Smart Citations